2015
DOI: 10.3389/fneur.2015.00163
|View full text |Cite
|
Sign up to set email alerts
|

CD8+ T Cell-Mediated Neuronal Dysfunction and Degeneration in Limbic Encephalitis

Abstract: Autoimmune inflammation of the limbic gray matter structures of the human brain has recently been identified as major cause of mesial temporal lobe epilepsy with interictal temporal epileptiform activity and slowing of the electroencephalogram, progressive memory disturbances, as well as a variety of other behavioral, emotional, and cognitive changes. Magnetic resonance imaging exhibits volume and signal changes of the amygdala and hippocampus, and specific anti-neuronal antibodies binding to either intracellu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 98 publications
1
15
0
Order By: Relevance
“…Between the subgroups of anti‐NMDAR AE and mixed AE cases, analysis revealed that good functional outcome and relapse rate following rituximab therapy were similar in both and mean mRS score reduction was significantly higher in former. Encephalitides with antibodies against intracellular antigens like LGI1, GAD, etc, are known to be mediated by T cells, while those with antibodies against surface antigens like NMDAR are known to be mediated by B cells 29,30 . Rituximab is a CD‐20 inhibitor with main action against the pan‐B‐cell marker CD 20 12 .…”
Section: Discussionmentioning
confidence: 99%
“…Between the subgroups of anti‐NMDAR AE and mixed AE cases, analysis revealed that good functional outcome and relapse rate following rituximab therapy were similar in both and mean mRS score reduction was significantly higher in former. Encephalitides with antibodies against intracellular antigens like LGI1, GAD, etc, are known to be mediated by T cells, while those with antibodies against surface antigens like NMDAR are known to be mediated by B cells 29,30 . Rituximab is a CD‐20 inhibitor with main action against the pan‐B‐cell marker CD 20 12 .…”
Section: Discussionmentioning
confidence: 99%
“…Consistently, following temporal lobe seizures induced by certain chemoconvulsants in mice, a successive accumulation of CD8 + T cells in the mesial temporal lobe with a strong impact on epileptogenesis has been observed. 30 Moreover, CD8 + T cells have been shown to dramatically affect neuronal excitability on the single cell and network level 31 33 and may thus well contribute to the neuronal pathology in LE. This possibility should be considered when stratifying immunotherapeutic approaches in GABA B -R LE.…”
Section: Discussionmentioning
confidence: 99%
“…The percentage of CD8+ T cells in the GAD antibody-mediated disease is intermediate (54%) [ 17 ]. The CD8+ T cells cause impairment of neuronal excitability and integrity with neuronal degeneration via two independent pathways: (1) granule cytotoxicity by perforin and granzyme-B and (2) ligation of death receptors [ 32 , 33 ]. Perforin is a Ca 2+ -dependent protein, which can form transmembranous pores, alter electrical excitability and signaling, and cause neuronal necrosis with swelling and rupture of cell membranes.…”
Section: Immunopathologymentioning
confidence: 99%